Digital Transformation and accessibility in Spanish Cooperative Banking: a study on the performance of their Websites - Fernández-Torres, Yakira; Palomo-Zurdo, Ricardo; Gutiérrez-Fernández, Milagros (REVESCO. Revista de Estudios Cooperativos, 2025)
Digitalization is an exponentially evolving process that has accelerated over the past 20 years, with particularly intense development in recent years. Financial institutions have had to adapt to this transformation to meet customer demands for fast, efficient access to financial services with an optimal user experience. This study focuses on proximity banking, using the cooperative banking sector as a reference due to its mutual ownership structure, predominantly retail nature, and strong territorial ties. Specifically, the 60 credit cooperatives operating in Spain as of December 31, 2022, were analyzed in order to characterize the services offered through their websites by examining their content. Based on a 115-item questionnaire, a statistical analysis was conducted to identify both the strengths of these websites—such as segmentation, communication channels, product offerings, and security—and the areas needing improvement, including the implementation of artificial intelligence, user identity recognition, and insufficient accessibility for people with disabilities, among others.